2022
DOI: 10.1007/s40261-022-01139-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tramadol Hydrochloride Twice-Daily Sustained-Release Bilayer Tablets with an Immediate-Release Component for Chronic Pain Associated with Knee Osteoarthritis: A Randomized, Double-Blind, Placebo-Controlled, Treatment-Withdrawal Study

Abstract: Background and Objectives Knee osteoarthritis pain is a chronic form of pain for which conventional non-steroidal anti-inflammatory drugs may provide insufficient analgesia. Twice-daily tramadol hydrochloride (65% sustained-release/35% immediate-release) bilayer tablets are a novel formulation of tramadol developed for managing chronic pain. The objectives of this study were to examine the effectiveness and safety of this formulation in patients with chronic knee osteoarthritis pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…During the treatment period, AEs were reported for 77.0% and 80.8% of patients in the bilayer tablet and IR capsule groups, respectively, while ADRs were reported for 58.7% and 53.6%, respectively. These values seem reasonable when we consider the frequencies of AEs reported in the initial open-label treatment escalation periods (80.6% and 78.7% in the knee osteoarthritis and postherpetic neuralgia studies, respectively) of two previous dose-withdrawal studies using the bilayer tablet formulation [11,12]. We enrolled opioid-naïve patients, which may increase the risk of opioid-related AEs and ADRs.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…During the treatment period, AEs were reported for 77.0% and 80.8% of patients in the bilayer tablet and IR capsule groups, respectively, while ADRs were reported for 58.7% and 53.6%, respectively. These values seem reasonable when we consider the frequencies of AEs reported in the initial open-label treatment escalation periods (80.6% and 78.7% in the knee osteoarthritis and postherpetic neuralgia studies, respectively) of two previous dose-withdrawal studies using the bilayer tablet formulation [11,12]. We enrolled opioid-naïve patients, which may increase the risk of opioid-related AEs and ADRs.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical guidelines position opioids, including tramadol, as options for managing cancer pain [4][5][6][7][8]. If acetaminophen or NSAIDs do not provide sufficient pain control, it may be possible to switch to these bilayer tramadol tablets, which have already shown good long-term efficacy and tolerability in patients with chronic non-cancer pain [10][11][12]. These bilayer tablets could be started early in the patient's clinical course and stepped down when no longer required, in accordance with WHO recommendations for the initiation, maintenance, and cessation of opioids [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetic studies have demonstrated that the immediate‐release component is rapidly absorbed and the maximum plasma concentrations of tramadol and its active metabolite (M1) were reached within 1–2.6 h after a single dose (NZ‐687‐I‐J1 pharmacokinetic study). The sustained‐release component is absorbed slowly and ensures the plasma tramadol trough concentrations are maintained at a stable, therapeutic level with twice‐daily administration 18 . As part of its clinical development, we performed a Phase III, randomized, double‐blind, placebo‐controlled, treatment‐withdrawal study to investigate the efficacy and safety of these bilayer tramadol tablets in patients with PHN.…”
Section: Introductionmentioning
confidence: 99%
“…The sustained-release component is absorbed slowly and ensures the plasma tramadol trough concentrations are maintained at a stable, therapeutic level with twice-daily administration. 18 As part of its clinical development, we performed a Phase III, randomized, doubleblind, placebo-controlled, treatment-withdrawal study to investigate the efficacy and safety of these bilayer tramadol tablets in patients with PHN.…”
Section: Introductionmentioning
confidence: 99%